Collectivism and individualism in US culture: An analysis of attitudes to group work - Mohammad Tamimy; Leila Setayesh Zarei; Mohammad Saber Khaghaninejad (Peoples' Friendship University of Russia (RUDN University), 2022)
Group work has recently gained attention in educational settings, and culture is an important factor influencing group work so the connection between the American culture and attitudes towards group work is worth studying. The present corpus-based study utilises the Corpus of Contemporary American English (COCA) to determine the current and the longitudinal traits of American cultural attitudes, which could influence the Americans' disposition towards collective activities including group work. Analysing the American discourse of different academic genres, it was revealed that while the American culture is predominantly individualistic, it has some potential for collectivism. Interestingly, it was observed that the American cultural is getting slightly less individualistic over time, especially after its individualistic soar in the second half of the 90s.